2010
DOI: 10.1016/j.neuroimage.2009.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sound intensity on tonotopic fMRI maps in the unanesthetized monkey

Abstract: The monkey's auditory cortex includes a core region on the supratemporal plane (STP) made up of the tonotopically organized areas A1, R, and RT, together with a surrounding belt and a lateral parabelt region. The functional studies that yielded the tonotopic maps and corroborated the anatomical division into core, belt, and parabelt typically used low-amplitude pure tones that were often restricted to threshold-level intensities. Here we used functional magnetic resonance imaging in awake rhesus monkeys to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…These fMRI studies are more consistent with our results based on multiunit FTCs in the anesthetized cat, and with the similar results of others (e.g., Heil et al 1994;Phillips et al 1994;Polley et al 2007), than with the level invariance inferred from responses to tones in awake monkeys by Sadagopan and Wang (2008). Interestingly, several fMRI studies in awake humans and monkeys that used complex tone stimulation have reported a less variable BOLD representation with sound level (Hall et al 2001;Tanji et al 2010). These studies also corroborate our findings based on the analysis of population spike and (especially) LFP responses to complex tones (LFPs are more related to the BOLD response than spikes, e.g., Logothetis et al 2001).…”
Section: Discussionsupporting
confidence: 93%
“…These fMRI studies are more consistent with our results based on multiunit FTCs in the anesthetized cat, and with the similar results of others (e.g., Heil et al 1994;Phillips et al 1994;Polley et al 2007), than with the level invariance inferred from responses to tones in awake monkeys by Sadagopan and Wang (2008). Interestingly, several fMRI studies in awake humans and monkeys that used complex tone stimulation have reported a less variable BOLD representation with sound level (Hall et al 2001;Tanji et al 2010). These studies also corroborate our findings based on the analysis of population spike and (especially) LFP responses to complex tones (LFPs are more related to the BOLD response than spikes, e.g., Logothetis et al 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Mechanisms for the representation of stimulus intensity or the corresponding percept of loudness however do not allow such an absolute encoding perceptually. They have been investigated using electroencephalography and brain imaging methods (Jancke et al 1998;Tanji et al 2010;Neuner et al 2014), but the existence of a dedicated encoding of intensity as the basis for an absolute and stable representation of the percept is uncertain. The absence of a correlation with loudness perception in contrast to the presence for those with pitch and time supports the notion that autistic traits relate to the ability to form a stable perceptual representation.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the question of how frequency tuning can be measured with fMRI, which requires the use of suprathreshold stimuli to illicit robust responses. Recent high-field fMRI studies (Petkov et al, 2006(Petkov et al, , 2009Tanji et al, 2010) using suprathreshold stimuli (70 -90 dB) have imaged multiple tonotopic fields in the macaque (including A1, R, RT, and belt areas) that matched the expected location, size, and gradient orientations known from previous electrophysiological and anatomical measures. As such, the BOLD response may be measuring (1) subtle preferences at high stimulus intensities and/or (2) the tuning of some neurons that remain sharp at high intensities.…”
Section: Measuring Tonotopy With Bold Fmrimentioning
confidence: 99%